Holocene deglaciation and glacier readvances on the Fildes Peninsula and King George Island (Isla 25 de Mayo), South Shetland Islands, NW Antarctic Peninsula. (June 2023) - Heredia Barión, Pablo; Roberts, Stephen J; Spiegel, Cornelia; Binnie, Steven A; Wacker, Lukas; Davies, Joanna; Gabriel, Imogen; Jones, Vivienne J; Blockley, Simon; Pearson, Emma J; Foster, Louise; Davies, Sarah J; et al.
To provide insights into glacier-climate dynamics of the South Shetland Islands (SSI), NW Antarctic Peninsula, we present a new deglaciation and readvance model for the Bellingshausen Ice Cap (BIC) on Fildes Peninsula and for King George Island/Isla 25 de Mayo (KGI) 62°S. Deglaciation on KGI began after c. 15 cal. ka BP and had progressed to within present-day limits on the Fildes Peninsula, its largest ice-free peninsula, by c. 6.6–5.3 cal. ka BP. Probability density phase analysis of chronological data constraining Holocene glacier advances on KGI revealed up to eight 95% probability 'gaps' during which readvances could have occurred. These are grouped into four stages – Stage 1: a readvance and marine transgression, well-constrained by field data, between c. 7.4 and 6.6 cal. ka BP; Stage 2: four probability 'gaps', less well-constrained by field data, between c. 5.3 and 2.2 cal. ka BP; Stage 3: a well-constrained but restricted 'readvance' between c. 1.7 and 1.5 cal. ka BP; Stage 4: two further minor 'readvances', one less well-constrained by field data between c. 1.3 and 0.7 cal. ka BP (68% probability), and a 'final' well-constrained 'readvance' after <0.7 cal. ka BP. The Stage 1 readvance occurred as colder and more negative Southern Annular Mode (SAM)-like conditions developed, and marginally stronger/poleward shifted westerly winds led to more storms and precipitation on the SSI. Readvances after c. 5.3 cal. ka BP were possibly more frequent, driven by reducing spring/summer insolation at 62°S and negative SAM-like conditions, but weaker (equatorward shifted) Westerlies over the SSI led to reduced storminess, restricting readvances within or close to present day limits. Late Holocene readvances were anti-phased with subaquatic freshwater moss layers in lake records unaffected by glaciofluvial inputs. Retreat from 'Neoglacial' glacier limits and the recolonisation of lakes by subaquatic freshwater moss after 1950 CE is associated with recent warming/more positive SAM-like conditions.